Bicuspid aortic valve in competitive athletes. Issue 1 (4th June 2007) - Stefani, L; Galanti, G; Toncelli, L; Manetti, P; Vono, M C; Rizzo, M; Maffulli, N
Abstract : Aim: Bicuspid aortic valve (BAV) is a common congenital cardiac condition. The presence of BAV in non-elite athletes has been poorly investigated; it is usually asymptomatic until valvular stenosis, regurgitation or other vascular alterations are evident. Design: Over a three-year period, 2273 competitive athletes were consecutively investigated with transthoracic echocardiography. The traditional parameters, the aortic root dimensions at four levels and the systolic and diastolic flow of aortic valve, were studied with continuous Doppler according to the echo guidelines. Setting: The study protocol included all the non-elite athletes investigated for the first evaluation to obtain eligibility. Patients: 2273 competitive athletes aged 8–60 years from several sports and regularly trained were evaluated with anamnesis, clinical check-up and echocardiography in order to exclude subjects with systemic or congenital heart disease. Results: BAV was diagnosed in 58 athletes (2.5%). Of these, nine had normal valvular function, 47 had abnormal valvular function with mild–moderate aortic regurgitation, and two had moderate stenosis. Aortic root dimensions at all levels were significantly greater in athletes with BAV than in athletes with a normal tricuspid valve. No relation was found with age, body surface area, aortic regurgitation or years of training. Conclusions: BAV is a relatively common congenital cardiac disease in athletes and commonly asymptomatic for a long time. This study suggests the usefulness of evaluating young athletes using echocardiography at least once when they start their sporting activity.